General population norms for the functional assessment of chronic illness therapy (FACIT)-fatigue scale - Montan, Inka; Löwe, Bernd; Cella, David; Mehnert-Theuerkauf, Anja; Hinz, Andreas (Value in health, 2018)
Background - The Functional Assessment of Chronic Illness Therapy (FACIT)-Fatigue Scale is an internationally used validated measure. General population-based age- and sex-specific percentile norms are, however, not published to date, although these are needed as reference for the interpretation of clinical research data. - Objectives - To assess the FACIT-Fatigue Scale in a large representative sample of the German general population to examine psychometric characteristics and factorial structure and to provide population-based norms. - Methods - A nationally representative face-to-face household survey was conducted in Germany using the FACIT-Fatigue Scale. Item characteristics were examined. Internal consistency was determined using the Cronbach α. Dimensionality was analyzed using confirmatory factor analysis (CFA) and bifactor analysis. Scale score differences relating to sex and age were assessed. Sex- and age-specific percentiles were computed for the entire scale range. - Results - Of 2426 participants, 55.7% were women, and the mean age was 49.8 ± 17.4 years. The FACIT-Fatigue Scale mean was 43.5 ± 8.3. Cronbach α was high at 0.92. Although fit indices of the CFA were below desired levels (root mean squared error of approximation = 0.144, comparative fit index = 0.846, and Tucker-Lewis index = 0.815), item loadings in the CFA and bifactor analysis confirm the scale’s unidimensionality. Women were more fatigued than men, and participants who were 70 years or older showed higher fatigue scores than younger respondents. Thus, sex- and age-specific population-based percentiles were provided. - Conclusions - Reliability and validity of the German translation of the FACIT-Fatigue Scale were confirmed. This study provides general population-based sex- and age-specific FACIT-Fatigue Scale percentile norms for the first time, thereby contributing to a meaningful interpretation of clinical research data.
Gesehen am 16.04.2020